Brieanna Hirsheimer: capstone - Hirsheimer, Brieanna, artist (Colorado State University. Libraries, 2019)
The artist's statement: I am interested in creating a sense of confusion in my viewer. Whether that be from questioning whether or not the piece is digital vs. painted, or a physical sense of vertigo as they are looking into an optical illusion. My paintings display a mixture of illusion, illustrative motifs and patterning that resemble digital art. I experiment with spray-paint, acrylic, oil, as well as collage. One aspect of my current work involves graphically painted subject matter occasionally resembling pop art. With this, I have found a new interest that meshes traditional styles with graphic design and pop elements. My recent work has been heavily influenced by optical phenomenons. With these illusions my goal is to create a visually intriguing space that the viewer wants to jump into. A space that has never been seen before but looks inviting, yet suggests the viewer be cautious. Evoking this complicated set of emotions is compelling to me, I want my work to cause the viewer to sift through these feelings while looking at (what seems to be) a rather simple piece. On top of illusion, street art, pop art, and graphic design also play a significant role in my work. It is rare that we connect these styles when thinking about the world of fine art as they are usually depicted as more simple and straightforward. It is my goal to stray away from this concept and move towards the idea of meshed styles as a form of fine art. These styles being looked at in this light have been a recent conversation, and I enjoy pushing that line in my own work. I have found that bold outlines and intense, bright colors seen in these types of art have become a staple in my paintings.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting